Inorganic nanoparticles for biomedical & technological applications - Menelaou, Melita (My University, 2022)
Magnetic nanoparticle (MNP)-based theranostics are emerging as important tools for diagnosis and treatment (theranostics) of various cancer types, and bone disorders. Synthesis of MNPs who can act as Magnetic Resonance Imaging contrast agents with high relaxivity and low toxicity is one of the major prerequisite in the field of theranostics [1]. Also, such applications require magnetic nanoparticles with well-defined composition, narrow size distribution, and high saturation magnetization values for enhanced interaction with an externally applied magnetic field. Spinel ferrites with the general formula MFe2O4 (M = Mn, Fe, Co, Ni) have been proposed among others to act of MRI contrast enhancement agents among other types of MNPs based on both transition metal ions and rare earth elements in the presence of various organic moieties, polymers, ligands, etc [2,3]. A facile solvothermal approach was used to synthesize stable ferrite nanoparticles as a simple and eco-friendly route, providing though products that exhibit high crystallinity in the presence of well-defined polymers and/or organic ligands. The hydrophobic MNPs converted to hydrophilic and the hyperthermic effects as well as relaxometric properties were studied and evaluated. Hydrophobic MFe2O4 nanoparticles coated with oleylamine (MFe2O4@OAm MNPs, where M = Co, Mn, Ni) with a similar shape and size (∼9 nm) and magnetization values of 87.4, 63.1 and 55.0 emu g−1 for CoFe2O4@OAm, MnFe2O4@OAm and NiFe2O4@OAm, respectively, were successfully encapsulated into the hydrophobic cores of spherical micellar structures formed by the copolymers in an aqueous solution through a solvent mixing procedure [4,5].
Keywords: Inorganic Nanoparticles